2003
DOI: 10.1074/jbc.m302386200
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin I-associated Phosphatidylinositol 3-Kinase Mediates Synaptic Vesicle Delivery to the Readily Releasable Pool

Abstract: Maintaining synaptic transmission requires replenishment of docked synaptic vesicles within the readily releasable pool (RRP) from synaptic vesicle clusters in the synapsin-bound reserve pool. We show that synapsin forms a complex with phosphatidylinositol 3-kinase (PI 3-kinase) in intact nerve terminals and that synapsinassociated kinase activity increases on depolarization. Disruption of either PI 3-kinase activity or its interaction with synapsin inhibited replenishment of the RRP, but did not affect exocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…In addition, PI3K activity seems to be involved in the establishment of neuronal polarity (Shi et al, 2003;Menager et al, 2004). While all these observations support the concept of PI3K-dependent vesicle exocytosis for axonal elongation, PI3K's functional role may be broader, as suggested by its interaction with microtubules and its involvement in the delivery of synaptic vesicles to the readily releasable pool (Cousin et al, 2003).…”
Section: Discussionmentioning
confidence: 50%
“…In addition, PI3K activity seems to be involved in the establishment of neuronal polarity (Shi et al, 2003;Menager et al, 2004). While all these observations support the concept of PI3K-dependent vesicle exocytosis for axonal elongation, PI3K's functional role may be broader, as suggested by its interaction with microtubules and its involvement in the delivery of synaptic vesicles to the readily releasable pool (Cousin et al, 2003).…”
Section: Discussionmentioning
confidence: 50%
“…It was shown that synapsin1-associated PI-3K regulates the size of the ready-releasable pool of synaptic vesicles [32]. Considering the essential role of PI-3K in ATP-dependent priming [59] and that PI-3K inhibitors can compete with PIP for the kinase ATP-binding site [81,95], inhibition of fusion extent seen here (Figs.…”
Section: Roles For Polyphosphoinositides In Regulated Releasementioning
confidence: 51%
“…Nevertheless neurosecretion from chromaffin cells was sensitive to both PI3K inhibitors at high concentrations. A recent study has highlighted a role for PI3K during synaptic vesicle exocytosis via a direct interaction of p85 with synapsin (Cousin et al, 2003). Interestingly, the concentration of PI3K inhibitors used in this study far exceeded that usually needed to inhibit PI3K type I.…”
Section: Differential Sensitivity To Pi3k Inhibitors Suggest a Role Fmentioning
confidence: 84%